Importance of acquiring knowledge through feedback in an emerging industry. Issue 2 (10th April 2017) - Duarte Alonso, Abel; Alexander, Nevil
Abstract : Purpose: The purpose of this paper is to investigate the importance of feedback in developing and operationalising knowledge from the perspective of craft brewing operators. The study contributes to various literature streams, including marketing and craft brewing entrepreneurship. An additional contribution is made through the adoption of the knowledge-based theory of the firm, and the SECI process to facilitate understanding of the significance of knowledge in the craft brewing industry. Design/methodology/approach: An online questionnaire was designed to gather data from mainly micro and small craft brewery operators. Of the 110 craft breweries identified across Australia, 57 (51.8 per cent) participated. The predominantly qualitative data were analysed using content analysis and word association. Findings: The importance of knowledge acquisition for craft brewery firms was revealed in various ways. For example, respondents most favoured new knowledge to learn about quality issues and perceptions of quality among buyers/consumers. Further, acquired knowledge through feedback was a determinant factor in participants' decision to produce particular styles of beers. Several alignments with the adopted theoretical frameworks were revealed, including the role of socialisation (SECI process) illustrated through the transformation of explicit into tacit knowledge. Originality/value: The study examines the dimension of knowledge in the craft brewing industry, which, although considerably developing, continues to be underresearched. Furthermore, the study's findings underline various important implications for the craft brewing industry, suppliers, and for end consumers. The study also proposes a refinement of both the RBTF and the SECI process based on the findings.